Теоретико-експериментальний метод розрахунку вагових коефіцієнтів штучної нейроподібної мережі в системах діагностування гідроагрегатів - Граняк, В. Ф.; Кацив, С. Ш.; Кухарчук, В. В.; Hraniak, Valerii; Katsyv, Samoil; Kukharchuk, Vasyl (Видавництво Львівської політехніки, 2019)
Запропоновано новий теоретико-експериментальний метод визначення вагових коефіцієнтів штучної нейронної мережі, якими слугують коефіцієнти взаємокореляції між просторово розподіленими вузлами гідроагрегату. Показано характер залежності коефіцієнтів кореляції від навантаження гідроагрегату і тиск води в резервуарі. Визначено, що в смугах частот, в яких зосереджені електродинамічні та гідродинамічні складові вібрації, суттєво змінюються коефіцієнти взаємокореляції вібросигналів у просторово рознесених квазісиметричних точках гідроагрегату. Це дає можливість розглядати коефіцієнти взаємокореляції як додаткову ознаку наявності електродинамічної та гідродинамічної складових вібрації в певній смузі частот.

In the article was proposed a new theoretical-experimental method for determining the weight coefficients of an artificial neural-like network. The authors propose using coefficients of correlation between the spatially distributed points of the hydro unit as these coefficients. The article contains theoretical substantiation of the dependence nature of the correction factors on the load of the hydro unit and the water pressure in the reservoir. These theoretical positions are confirmed by experimental research. This research was carried out at the industrial equipment of the Hydro power station. A serious problem in frequency analysis of vibration signals of hydro units consists in the non-periodical character of the signals. Therefore, is proposed an original method for determining the coefficients of correlation between the spatially distributed points of the hydro unit. It involves the prior use of a wavelet transformation. In the course of an experimental research it was found that that the dependence of the coefficients of correlation between the pressures of water in the reservoir at low frequencies is due to the dependence of the lapidary flow from the pressure of water in the reservoir. The reason for the change in the coefficients of inter-correlation in the thirteenth frequency band is the cavitations phenomenon. As a result of the research, it has been proved that in the indicated frequency bands, the coefficients of the correlation of vibration signals in the spatially distributed quasi-symmetric points of the hydro aggregate change significantly when the water pressure in the reservoir changes. This makes it possible to consider them as an additional sign of the presence of the hydrodynamic component of the vibration.
Theoretical-experimental method of calculation ofweight coefficients of the artificial neural-like network in diagnostic systems of hydroagregates
Keywords: штучна нейроподібна мережа; амплітудно-частотно-часовий спектр; смуга частот; чинник вібрації; показник вірогідності; коефіцієнт кореляції; ваговий коефіцієнт; Artificial neural-like network; Amplitude-frequency-temporal spectrum; Frequency band; Vibration factor; Probability index; Coefficient of correlation; Weighted coefficient